Physical fitness of taekwondo athletes - A.Rashid, Noorul Husna (Universiti Sains Malaysia, 2009)
The purpose of this study was to assess physical frtness in young Kelantanese taekwondo-in. The participants were eight male (18.63 ± 1.92 yrs, 168.65 + 7.36 em, 68.29 ± 20.69 kg) and ten female (18.10 ± 1.37 yrs, 158.22 ± 4.11 em, 59.72 ± 10.03 kg) taekwondo athletes. Weight, height and body composition were the anthropometric measurement that were assessed according to ISAK guidelines. The physical fitness characteristics that were evaluated included aerobic endurance by the PACER test, muscular strength and endurance by sit-ups as well as push-ups, explosive power by the vertical jump and flexibility by the modified sit-and-reach test. The females had a higher relative percent total body fat with moderate effect (p < 0.001, eta2 = 0.566) while males had more lean body mass (p = 0.005) but this difference was small (eta2 = 0.399). There was no difference between males and females in right (p = 0.355, eta2 = 0.054) and left leg flexibility (p = 0.142, eta2 = 0.130). The males jumped higher than the females (p = 0.001) but the effect was small (eta2 = 0.476). The difference became smaller when scaled for height (m2): 17.39 ± 3.07 em for males and 14.25 ± 1.66 em for females (p = 0.020, eta2 = 0.331). The theoretical exponent for height controlled for the effect of the body size variable relative to the vertical jump in the males (r =- 0.08, p = 0.864) but not in the females (r = -0.71, p = 0.033). When the vertical jump was expressed in terms of LBM (kg0 · 67 ), the difference between males and females disappeared (p = 0.179, eta2 = 0.125): 3.52 ± 0.88 em versus 3.06 ± 0.41 em. The theoretical exponent for height controlled for the effect of the body size variable relative to the vertical jump in the males (r = -0.66, p = 0.1 09) but not in the females (r = -0.83, p = 0.006). There was no difference between males and females in push-ups (p = 0.244. ES = 0.466) as well as in the sit-ups (p = 0.809, ES = 0.127). The males had a higher aerobic endurance (p = 0.003, eta2 = 0.453). Male taekwondo-in have higher aerobic endurance, higher explosive power and less percent body fat.